Artificial Intelligence in Stem Programs to Develop Human Capital - Hernández, Sonia Benito; Shahy, Rouhollah Iran (International Journal on Human-Computing Studies, 2025)
This study analyzes the use of artificial intelligence (AI) tools by students at the Technical University of Madrid (Spain) in science and engineering disciplines, based on a survey of 94 participants. The objective was to identify usage patterns and their relationships with variables such as academic performance, perceived learning, ethics, trust, knowledge, and recommendation. Descriptive statistics and association tests (e.g., chi-square, the Phi, and Cramér’s V) were used to assess the strength of the relationships between categorical variables. The results show that most students have used AI tools for academic purposes and report a positive perception in terms of learning and knowledge. Significant associations were found between AI use and learning-related variables, while others like academic performance and trust did not show statistical significance. Minor gender-based differences were observed, but not statistically significant. These findings suggest a growing normalization of AI use in technical education, where perceptions of usefulness and ethics outweigh the impact on academic performance. The implications are discussed within the framework of designing pedagogical strategies for the responsible integration of AI in higher education.